Reproductive dynamics of the invasive lionfish (Pterois miles) in the Eastern Mediterranean Sea. Issue 2 (20th December 2021) - Mouchlianitis, Foivos A.; Kalaitzi, Georgia; Kleitou, Periklis; Savva, Ioannis; Kletou, Demetris; Ganias, Kostas
Abstract: The lionfish Pterois miles invaded the Mediterranean Sea in 2012 and spread fast to the entire eastern basin. This study provides evidence of successful spawning and the first detailed analysis of P. miles ovarian dynamics in the Mediterranean Sea. The ovarian reproductive phases of mature females collected from Cyprus (eastern Mediterranean) between September 2017 and August 2018 were analysed, both macroscopically and histologically. The results suggested a prolonged oocyte recruitment and development season, and a spawning season that primarily occurred during summertime, even though spawning‐capable females were caught also in autumn. A year‐round spawning activity may have been inhibited due to seasonal variations in water temperature. Multiple oocyte developmental stages co‐occurred in females at different reproductive phases, indicating that more than one oocyte batches were released per spawning season. The analysis of the spawning batch formation enabled the batch fecundity estimation at 3225–63149 oocytes. The oocyte development pattern described in this study shared characteristics with the indeterminate fecundity type, where new oocytes are recruited to the secondary growth phase in parallel with spawning activity. Climate change is likely to extend the spawning season of lionfish in the Mediterranean Sea and further favour its invasion. The information provided in this study is vital for the design of strategic and effective management plans to restrain the expansion of this highly invasive fish.